1996
DOI: 10.3109/00016359609003502
|View full text |Cite
|
Sign up to set email alerts
|

Mineral loss in incipient caries lesions quantified with laser fluorescence and longitudinal microradiography: A methodologic study

Abstract: Månsson (1996) Mineral loss in incipient caries lesions quantified with laser fluorescence and longitudinal microradiography: A methodologic study, Acta Odontologica Scandinavica, 54:1, 8-13To link to this article: http://dx.loss in incipient caries lesions quantified with laser fluorescence and longitudinal microradiography. A methodologic study. Acta Odontol Scand 1996;54:8-13. Oslo. ISSN 0001-6357.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 12 publications
(8 reference statements)
2
47
0
3
Order By: Relevance
“…[18][19][20][21] In brief, the QLF system's ability is to accurately determine mineral content of enamel.…”
Section: Combination Of Camera and Fluorescence Systemsmentioning
confidence: 99%
“…[18][19][20][21] In brief, the QLF system's ability is to accurately determine mineral content of enamel.…”
Section: Combination Of Camera and Fluorescence Systemsmentioning
confidence: 99%
“…The quantitative light-induced fluorescence (QLF) method that recently came on the market (Inspektor™ Pro) in several countries can readily detect lesions to a depth of approximately 500 μm on smooth and occlusal enamel surfaces. The QLF method has been tested in several in vitro, [32][33][34] in situ, 35 and in vivo 36-41 studies for smooth surface caries lesions. The possibility of adapting the QLF method for occlusal caries diagnosis is under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…A recent in vitro study comparing fluorescence loss in white spot lesions after initial demineralization and after various remineralization protocols has shown that fluorescence loss for the remineralized lesions and the original lesions have the same linear relation with mineral loss. 35 This, together with the fact that natural caries lesions also show the same relation between fluorescence loss and mineral loss, 27 gives us a good indication that QLF is suited for the assessment of the remineralization process as well.…”
Section: A Inspektor Pro™: Quantitative and Qualitative Assessmentmentioning
confidence: 99%
“…While the technique was validated both quantitatively by comparison with mineral loss and lesion depth from transverse or longitudinal microradiography [22][23][24][25][26][27][28] and qualitatively by comparison with visual detection and histology [29][30][31][32][33][34] the true strength of the technique is not its capability to detect lesions but to follow the oral health over time. The images or series of longitudinal images of a tooth over an extended period in time, can be analyzed for GF loss and presence of RF.…”
Section: A Inspektor Pro™: Quantitative and Qualitative Assessmentmentioning
confidence: 99%